2019
DOI: 10.1371/journal.pone.0214438
|View full text |Cite
|
Sign up to set email alerts
|

Importance of modelling decisions on estimating trajectories of depressive symptoms and co-morbid conditions in older adults: Longitudinal studies from ten European countries

Abstract: Background International comparisons of trajectories of depressive symptoms in older adults are scarce and longitudinal associations with co-morbid conditions not fully understood. Objective To compare trajectories of depressive symptoms from participants living in 10 European Countries and identify ages at which the associations of co-morbid conditions with these trajectories become more relevant. Methods Latent growth curve models were fitt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Fourteen out of eighteen studies carried out in a community setting found that multimorbidity was positively related to depressive symptoms over time. For example, the largest study (Marroig et al, 2019) The results showed a significant positive association between multimorbidity across time and the average number of depressive symptoms at ages 60, 65 and 70 in all countries studied. One study from the US (Sutin et al, 2013) with a follow-up duration of 30 years investigated the trajectory of depressive symptoms and associated factors that may contribute to increases in depressive symptoms across adulthood.…”
Section: Multimorbidity and Change Of Depressive Symptomsmentioning
confidence: 89%
See 2 more Smart Citations
“…Fourteen out of eighteen studies carried out in a community setting found that multimorbidity was positively related to depressive symptoms over time. For example, the largest study (Marroig et al, 2019) The results showed a significant positive association between multimorbidity across time and the average number of depressive symptoms at ages 60, 65 and 70 in all countries studied. One study from the US (Sutin et al, 2013) with a follow-up duration of 30 years investigated the trajectory of depressive symptoms and associated factors that may contribute to increases in depressive symptoms across adulthood.…”
Section: Multimorbidity and Change Of Depressive Symptomsmentioning
confidence: 89%
“…, 2007Fauth et al, 2012;Stommel et al, 2004;Turuba et al, 2019;Wu et al, 2012) focused on older adults aged 65 and above and the rest on individuals aged 50 and above. The percentage of females ranged from 45.6% to 72%, although the proportion was unclear in four studies (Chou, 2008;Marroig et al, 2019;Roberts et al, 1997; (Table 4.1).…”
Section: Data Extraction and Quality Assessmentmentioning
confidence: 98%
See 1 more Smart Citation
“…These issues are not always insurmountable, and indeed can be an asset when handled appropriately, but do require mindful decision making and transparency. It is also important to keep in mind that, with any analysis, including coordinated analysis, differences in modeling decisions will have potential impacts on the output obtained and the conclusions drawn (Marroig et al, 2019).…”
Section: The Importance Of Coordinated Analysismentioning
confidence: 99%